2018
DOI: 10.1101/475491
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vascular physiology drives functional brain networks

Abstract: ABSTRACTWe present the first evidence for vascular regulation driving fMRI signals in specific functional brain networks. Using concurrent neuronal and vascular stimuli, we collected 30 BOLD fMRI datasets in 10 healthy individuals: a working memory task, flashing checkerboard stimulus, and CO2 inhalation challenge were delivered in concurrent but orthogonal paradigms. The resulting imaging data were averaged together and decomposed using independent compone… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…However, in principle, nuisance fluctuations could give rise to similar spatial patterns as neurally-driven fluctuations. A recent study by (Bright et al, 2018) provided evidence that physiological fluctuations (end-tidal CO 2 ) give rise to networks that spatially resemble neurally-driven networks linked to working memory and visual stimuli. The authors suggested that this phenomenon may be due to the vasculature adapting to the neural network architecture, as vascular and neuronal growth processes evolve concurrently during development (Quaegebeur et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, in principle, nuisance fluctuations could give rise to similar spatial patterns as neurally-driven fluctuations. A recent study by (Bright et al, 2018) provided evidence that physiological fluctuations (end-tidal CO 2 ) give rise to networks that spatially resemble neurally-driven networks linked to working memory and visual stimuli. The authors suggested that this phenomenon may be due to the vasculature adapting to the neural network architecture, as vascular and neuronal growth processes evolve concurrently during development (Quaegebeur et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, in principle, nuisance fluctuations could give rise to similar spatial patterns as neurally-driven fluctuations. A recent study by (Bright et al, 2018) provided evidence that physiological fluctuations (end-tidal CO 2 ) give rise to networks that spatially resemble neurallydriven networks linked to working memory and visual stimuli. The authors suggested that this phenomenon may be due to the vasculature adapting to the neural network architecture, as vascular and neuronal growth processes evolve concurrently during development (Quaegebeur et al, 2011).…”
Section: 2mentioning
confidence: 99%
“…Bright MG, Whittaker JR, Driver ID, Murphy K. 2018. Vascular physiology drives functional brain networks.…”
mentioning
confidence: 99%